Complications after radiofrequency ablation of hyperparathyroidism secondary to chronic kidney disease - Li-Ping Lin; Miao Lin; Song-Song Wu; Wei-hua Liu; Li Zhang; Yi-ping Ruan; Mei-zhu Gao; Fu-Yuan Hong (Renal Failure)
Objective To study the complications of ultrasound-guided radiofrequency ablation (RFA) in chronic kidney disease (CKD) patients undergoing renal replacement therapy with secondary hyperparathyroidism (SHPT).Methods This retrospective study reviewed the clinical data, including general information, examination results, treatment times, time interval, and postoperative complications, of 103 SHPT patients who received ultrasound-guided RFA treatment from July 2017 to January 2021.Results Of 103 patients, 52 required two sessions of RFA within a month. The incidence of recurrent laryngeal nerve injury at the second treatment was significantly higher than that at the first treatment (first session vs. second session, 5.77% vs. 21.15%; p = .021). Of all the enrolled 103 patients, 27 suffered complications after the first session of RFA. When we separated patients into complications group and non-complication group, we detected more ablated nodules in the complications group (Z = −2.222; p = .0026). Subgroup analysis further showed that the patients in the severe hypocalcemia group were younger (p = .005), had more ablated nodules (p = .003) and higher blood phosphorus (p = .012) and alkaline phosphatase (ALP) levels (p = .002). Univariate analysis showed that age, serum phosphorus, ALP, and number of ablated nodules were associated with a higher risk of severe hypocalcemia after the first session of RFA.Conclusions An interval of more than 1 month between two treatments may help to avoid recurrent laryngeal nerve injury. Age, serum phosphorus, ALP, and number of ablated nodules were associated with a higher risk of severe hypocalcemia after the first session of RFA.